(3HZjI GdQGei TQM GdefXheI aj GdQei HGdfTGHs - (3WjHZG GdCTQai GdHcGTi GdjhfGfis
(3ChdgG (B:s
(3GdMeO ddg GdYGOd Mceg GdTGed Ydeg GdbGgQ SdWGfg GdHGgQ HQgGfg s
(3BNQgG (B:s
(3ef jgOi Gddg agh GdegJOi hef jVdd adf JLO dg hdjkG eQTOkG hdGMhd hdGbhI EdG HGddg GdYdi GdYXje hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde s
(3fSNI KGfjIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B93) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs